Oral Health-Related Quality of Life and Satisfaction Following Implant Restoration After Sinus Floor Augmentation: A Prospective Evaluation - Nguyen, Hoang Giang; Nguyen, Ly Dien Truc; Le, Lam Nguyen; Vo, Van Nhan (Scripta Medica, 2026)
Background/Aim: Alveolar ridge resorption and maxillary sinus pneumatisation present significant challenges for implant rehabilitation. Although lateral window sinus floor augmentation (LWSFA) is a predictable surgical approach, patient-reported outcomes remain essential for evaluating treatment success beyond osseointegration. This study aimed to evaluate longitudinal oral health-related quality of life (OHRQoL) and satisfaction in patients undergoing implant therapy after LWSFA. Methods: This prospective longitudinal study included 39 patients with 57 posterior maxillary edentulous sites and residual bone height ≤4 mm. All patients underwent LWSFA using a mixture of allograft, synthetic bone substitute and platelet-rich fibrin. After six months of graft maturation, implants were placed, followed by definitive prosthetic restoration after a further six months. OHRQoL was assessed using the Oral Health Impact Profile-14 (OHIP-14) at baseline and at one week, six months and 12 months after functional loading. Patient Satisfaction Score (PSS) was measured using a visual analogue scale. Results: Mean OHIP-14 scores improved significantly from 24.28 ± 9.77 at baseline to 6.13 ± 2.82 at 12 months (p < 0.001). Most domain-specific improvements appeared to stabilise by six months. PSS increased significantly from 8.92 ± 0.81 at one week to 9.44 ± 0.55 at six months (p < 0.017), before reaching a plateau. Across all time points, female patients consistently reported significantly higher OHIP-14 scores than males (p < 0.05). Satisfaction in single-tooth cases stabilised within one week, whereas multi-unit cases required six months. Conclusion: LWSFA followed by implant-supported restoration significantly improves OHRQoL and satisfaction. Maximum satisfaction and functional comfort are typically achieved and sustained after six months of functional loading.